Correction: The effect of M. tuberculosis lineage on clinical phenotype - Du, Duc Hong; Geskus, Ronald B.; Zhao, Yanlin; Codecasa, Luigi Ruffo; Cirillo, Daniela Maria; Crevel, Reinout van; Pascapurnama, Dyshelly Nurkartika; Chaidir, Lidya; Niemann, Stefan; Diel, Roland; Omar, Shaheed Vally; Grandjean, Louis; et al. (PLOS global public health, 2024)
[This corrects the article DOI: 10.1371/journal.pgph.0001788.].